Exploring the Barriers of Net Zero Energy Buildings (NZEBS) Implementation in Malaysia: Perception of Malaysian Construction Practitioners - Abdellah, Roy Hazli; Masrom, Md Asrul Nasid (International Journal of Integrated Engineering, 2019)
Malaysia is a country which is undergoing a booming phase of urbanization. However, the rapid development in the construction sector leads to major concerns on sustainability for this sector. For instance, the increase volume of carbon dioxide emissions, climate change, depletion of resources as well as excessive of waste generation. Besides that, it is beyond doubt that energy invested in building construction has a significant threat towards climate change and sustainability, thus by addressing the issues on energy in building sector, the net zero energy buildings (NZEBs) has emerges to be an important concept to confront with these issues. However, previous studies found that the Malaysian construction industry is still unfamiliar with the concept of NZEBs. Therefore, the purpose of this paper is to investigate the barriers of NZEBs implementation in Malaysia based on a review of the existing literature and by utilising semi-structured interviews with 5 experienced practitioners. The result of this paper indicates that there are three barriers areas that need to be consider which are cost barriers, technical and technologies barriers, and government policies barriers. This study provides an exciting opportunity to advance our knowledge of barriers that will exists in the Malaysian construction industry context.